Silver-catalyzed C- to N-center remote arene migration - Ning, Y; Mekareeya, A; Babu, K; Anderson, E; Bi, X (American Chemical Society, 2019)
The 1,4-arene migration from a carbon to a nitrogen center, induced by iminyl radicals generated from radical additions to vinyl azides, is reported. Two different modes of vinyl azide activation trigger this migration process, which offers a mild route for the synthesis of trifluoromethyl- or sulfonyl-substituted β-enamino ketones. Mechanistic studies reveal a dual role for the silver catalyst and provide insight into the nature of the migration by demonstrating the positional influence of arene substituents on arene migratory aptitude. By in situ generation of the key migration substrate from readily available precursors, this method offers a novel strategy for achieving remote C- to N-group migration, and more generally for the formal activation of C–C bonds.